Study on growth of Aloe vera by Using Different Growth Media - Salitxay, Timnoy; Sitthivohane, Insavai; Langsouapha, Aomxai (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This study aimed to study on growth and Survival rate of Aloe by using different growing media. In addition, appropriate substrate for Aloe was also studied. By using Randomized Complete Block Design (RCBD), 4 treatments (T1: Soil; T2: Soil+ cocnut coir+ Charcoal+ chicken manure); T3: Soil+ 50% burned husk + sand+ chicken mnure; T4: Soil+ Coconut coir + Brick+ chicken manure) were used. Data was collected 2 weeks of intervals until 8 weeks of data collecting duration. The results revealed that, T4 showed the best data on growth parameters (Plant height 21.10 cm, leave width 1.32 cm, leave length 12.27 cm, and Leave number 8.70 at 8 week of growing duration). Whereas, T3 showed lowest response on growth parameters (Plant height, leave width, leave length, and Leave number were 14.51 cm, 1.15 cm, 11.38 cm, and 7.50 leaves, respectively during 8 week of data collection). Overall, every treatment showed good data on survival rate (100%)